Theoretical concept of Istihalah in gelatine application: A review - Halimah, Ab. Rahim; Hasan, Ahmad; Mohd Hasbi, Ab. Rahim (AL-QIYAM Centre for Scientific Research and Studies, 2020)
This paper will appraise the literature regarding Istihalah theory in gelatine application according to Islamic perspectives. With the development of food technology, variety of food additives have been produced and become issues due to the non-halal raw material being used. One of the examples is porcine gelatine that is come from the non halal pig bones, skin, tendon, connective tissues and cartilages. The Istihalah processes of gelatine were clarified and categorized as istihalah sahihah (complete transformation) or istihalah fasidah (imperfect transformation) based on views from the fiqh scholars and scientific study. Gelatine as a food additives that apply with Istihalah process were discussed theoretically and scientifically to unravel these issues. The study methods adopt qualitative analysis by referring the primary evidence from al-Quran, al-Sunnah, al-Ijma’, al-Qiyas and also secondary evidence from credible sources such as fiqh books, food science books, websites and other related resources.